2021
DOI: 10.1049/bme2.12048
|View full text |Cite
|
Sign up to set email alerts
|

Failure of affine‐based reconstruction attack in regenerating vascular feature points

Abstract: Inverse biometrics methods are a major privacy concern for users of biometric recognition systems. Affine‐based reconstruction attack is an inverse biometrics method that models the biometric recognition algorithm by an affine approximation. This type of attack reconstructs targeted biometric references using the modelled biometric recognition algorithm and the comparison scores issued by the system. Although this reconstruction method has only been successfully applied to reconstruct face images, the common c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Thus, it is worth evaluating the threat of the MSK reconstruction attack on our proposed system. We have previously showed that this attack fails in reconstructing retinal point pattern templates (the nodes of our graph templates) and retinal images, when point pattern comparison algorithms are applied [18], [19]. Here, we show the attack fails in reconstructing the retinal images and consequently graph pattern when BGC is used as the comparison algorithm.…”
Section: Irreversibility Of Dissimilarity Vectorsmentioning
confidence: 65%
See 3 more Smart Citations
“…Thus, it is worth evaluating the threat of the MSK reconstruction attack on our proposed system. We have previously showed that this attack fails in reconstructing retinal point pattern templates (the nodes of our graph templates) and retinal images, when point pattern comparison algorithms are applied [18], [19]. Here, we show the attack fails in reconstructing the retinal images and consequently graph pattern when BGC is used as the comparison algorithm.…”
Section: Irreversibility Of Dissimilarity Vectorsmentioning
confidence: 65%
“…6(a) represents the distribution of scores for reconstructed reference images. For 2. https://github.com/mahshidsa/Irreversibility-DissimilarityVector-Retina.git a successful reconstruction, it is expected from the distribution of scores for reconstructed images to overlap with the distribution of scores for mated comparison trials (similar to what was shown for face images in [19]). However, as can be seen in Fig.…”
Section: Irreversibility Of Dissimilarity Vectorsmentioning
confidence: 67%
See 2 more Smart Citations